Penggunaan Model Concept Sentence untuk Meningkatan Prestasi Belajar Peserta Didik - Nurhidayah, Yulli; Herlina, N. Hani; Aziz, Abdul (Jurnal Penelitian Pendidikan Islam, 2016)
This research is motivated by the lack of student learning outcomes in social studies. In an effort to improve student achievement, researchers used the concept learning model sentences. The method used is classroom action research “Dave Ebbut” models. Data collection technique used observation and written tests. The results showed an increase in student learning outcomes in the first cycle with an average value of 68.65 with the percentage of students completeness 46%, the second cycle was obtained an average value of 74.8 students with the percentage of completeness 76%, and the third cycle values obtained an average of 78.5 students with a percentage to reach 92% level of completeness.